2014
DOI: 10.3928/00220124-20140825-20
|View full text |Cite
|
Sign up to set email alerts
|

The Dementia Friendly Hospital Initiative Education Program for Acute Care Nurses and Staff

Abstract: Individuals with Alzheimer’s disease and other dementias have 3.2 million hospital stays annually, which is significantly more than older individuals without dementia. Hospitalized patients with dementia are at greater risk of delirium, falls, overwhelming functional decline that may extend the hospital stay, and prolonged and/ or complicated rehabilitation. These risks support the need for staff education on the special care needs of this vulnerable population. In this article we describe a full-day education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
95
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(96 citation statements)
references
References 9 publications
(9 reference statements)
1
95
0
Order By: Relevance
“…Even if dementia is recognized by NAs/AHWs (which is not always the case), the care provided often does not meet standards of person-centered, best practice approaches that can alleviate the consequences of the behavioral, psychiatric, and emotional symptoms related to cognitive impairment in acute care settings (Clissett et al, 2013; Gaugler & Wocken, 2014). Such gaps in care suggest the need for increased and enhanced training for NAs/AHWs to improve skills, knowledge, and confidence, with the aim of enhancing quality of care overall for individuals with dementia (Bray et al, 2015; Elvish et al, 2016; Gillies et al, 2015; Luxford et al, 2015; Palmer et al, 2014; Smythe et al, 2014; Surr et al, 2016; Teodorczuk et al, 2014). The current study contributes to this area by presenting a more portable, potentially cost-efficient approach to training NAs/AHWs in hospitals via the CDFH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if dementia is recognized by NAs/AHWs (which is not always the case), the care provided often does not meet standards of person-centered, best practice approaches that can alleviate the consequences of the behavioral, psychiatric, and emotional symptoms related to cognitive impairment in acute care settings (Clissett et al, 2013; Gaugler & Wocken, 2014). Such gaps in care suggest the need for increased and enhanced training for NAs/AHWs to improve skills, knowledge, and confidence, with the aim of enhancing quality of care overall for individuals with dementia (Bray et al, 2015; Elvish et al, 2016; Gillies et al, 2015; Luxford et al, 2015; Palmer et al, 2014; Smythe et al, 2014; Surr et al, 2016; Teodorczuk et al, 2014). The current study contributes to this area by presenting a more portable, potentially cost-efficient approach to training NAs/AHWs in hospitals via the CDFH.…”
Section: Discussionmentioning
confidence: 99%
“…To help improve hospital-based dementia care, several educational programs and approaches (often provided over the course of several days) have attempted to enhance NAs’/AHWs’ training (Bray et al, 2015; Elvish et al, 2016; Galvin et al, 2010; Gillies, Coker, Montemuro, & Pizzacalla, 2015; Luxford et al, 2015; Palmer et al, 2014; Surr, Smith, Crossland, & Robins, 2016; Teodorczuk, Mukaetova-Ladinska, Corbett, & Welfare, 2014). However, dissemination of evidence-based training has been limited due to the necessity of costly in-person delivery.…”
mentioning
confidence: 99%
“…In the single study where delivery methods were well described, content specific to prevention and management of emotional stress experienced by patients with dementia-related NDB was not evident. 53 …”
Section: Literature Reviewmentioning
confidence: 99%
“…As well [19], Canada, who indicated that, significant improvement on the posttest participants' attitudes, practices, confidence, and knowledge [14], emphasized that the highest percentage of nurses' knowledge were unsatisfactory and immediately improved after implementation of the guidelines.…”
Section: Discussion Of the Study Findings Are Categorized Under The Fmentioning
confidence: 99%